2012
DOI: 10.1159/000338907
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of a Disposable Home Urinary Flow Measuring Device as a Diagnostic Tool in the Management of Males with Lower Urinary Tract Symptoms

Abstract: Introduction: To investigate the accuracy of uroflowmetry with disposable QSingle compared to measurements with a home-based digital device and compared to a single clinical measurement. Patients and Methods: 60 men with lower urinary tract symptoms were included in a prospective, open-label, multicenter study. Uroflowmetry measurements were done using three devices/methods: single clinic-based method, followed by up to 12 measurements using the disposable home-based QSingle and up to 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
(12 reference statements)
2
9
0
Order By: Relevance
“…The findings from this study may be used to promote the development of various devices in different formats. The disposable home device proposed by Heesakkers et al [ 20 ] was used to measure urinary symptoms in male patients with LUTS. They developed and analyzed the device by focusing on Q max and reported the findings from the analysis after using the device on 59 male patients.…”
Section: Discussionmentioning
confidence: 99%
“…The findings from this study may be used to promote the development of various devices in different formats. The disposable home device proposed by Heesakkers et al [ 20 ] was used to measure urinary symptoms in male patients with LUTS. They developed and analyzed the device by focusing on Q max and reported the findings from the analysis after using the device on 59 male patients.…”
Section: Discussionmentioning
confidence: 99%
“…Q Single (AstraTech AB, Mölndal, Sweden) was developed as a single-use UFM device for home use in order to provide simple Qmax and Vvoid measurements [30]. As illustrated in Fig.…”
Section: Home Uroflowmetersmentioning
confidence: 99%
“…(A) Uflow Meter (MDTi, Wolverhampton, UK) [20], (B) Peakometer [20], (C) P-flow meter [20], (D) Q Single device (AstraTech AB, Mölndal, Sweden) [30], and (E) Da Capo [20]. …”
Section: Figmentioning
confidence: 99%
“…In addition, it has been reported that measurement at home is necessary. [2][3][4][5][6][7] However, this mode of urine measurement is not very popular in homes because, in Japan, homebased urine flow measurement cannot be claimed as an insured mode of medical treatment; its value for home use is not well known. Many urine flowmeters often store urine in containers.…”
Section: Introductionmentioning
confidence: 99%
“…Hospitals tend to use a fixed type of uroflowmeter, which is often installed in the toilet; in this context, it may not be possible to obtain accurate measurements because of tension during examinations. In addition, it has been reported that measurement at home is necessary 2‐7 . However, this mode of urine measurement is not very popular in homes because, in Japan, home‐based urine flow measurement cannot be claimed as an insured mode of medical treatment; its value for home use is not well known.…”
Section: Introductionmentioning
confidence: 99%